On the random integral equation with advancing argument - Gacki, Henryk (Annales Mathematicae Silesianae, 1985)
In this paper the existence and uniqueness of stochastic solutions of equation (1) are presented. Our theorem is an application of Banach fixed point theorem to the integral equation with advancing argument.